Serverless Computing Architecture Security and Quality Analysis for Back-end Development (Journal of The Colloquium for Information Systems Security Education, 2020)
The purpose of this paper is to propose how to improve both quality and security for the back-end of a modern software system through adapting to the serverless computing architecture. For this purpose, this paper will conduct the following three steps: 1) Show a complete back-end architecture using three serverless computing such as Amazon Web Service (AWS), Microsoft Azure (Azure), and Google Cloud Platform (GCP). 2) Analyze each component's security and quality of each serverless computing provider and compare it to show similarities and differences. 3) Describe how using a cloud service improves the quality and security of a system.
Keywords: Serverless Development; Amazon Web Services; Microsoft Azure; Google Cloud Platform; Security Design; Quality Improvement